PERANCANGAN JARINGAN RT/RW NET DENGAN FIBER OPTIK BERBASIS MIKROTIK DI FAQIH TEKNOLOGI - Muhammad Khaidir Fahram; Vina Vijaya Kusuma; Wahyu Firmansyah (LPPM Unbaja, 2025)
The development of information technology continues to increase, driving people's need for fast and affordable internet access. However, rural communities often face obstacles such as weak GSM signals and expensive data plan fees. To overcome these challenges, fiber optic-based RT/RW Net networks are a promising solution, offering stability and high speed at a lower cost than wireless networks. Faqih Teknologi, a micro-enterprise, delivered the Internet Masuk Desa program in Karang Suraga. Despite initially using wireless technology, the company faced obstacles such as vulnerability to lightning, signal interference due to weather and geographical factors, and high maintenance costs. Switching to fiber optic overcame these issues, offering a more stable signal, lower susceptibility to weather, and more efficient maintenance costs. This research uses the Network Development Life Cycle (NDLC) method to design a fiber optic-based internet network system. The NDLC stages include requirements analysis, network design, simulation, implementation, monitoring, and management. This approach ensures that the designed system is able to meet the needs of the community with optimal performance, while opening up new economic opportunities for the community through a partnership-based business model.